Certain problems of noise annoyance - Aurelian STAN (Archives of Acoustics)
Of many objective and subjective problems connected with noise annoyance the present paper presents the results of investigations concerning the following issues: 1. Dependence of the effectiveness of an acoustic baffle on the kind of closed space in which it has been placed. 2. Economic effects of measures taken to diminish noise inside a closed space. 3. Correlation between certain annoyance indices TNI and LNP and σ, the presentation of results of statistical traffic noise measurements.